Directional Single‐Photon Emission from Deterministic Quantum Dot Waveguide Structures. Issue 8 (22nd June 2020) - Mrowiński, Paweł; Schnauber, Peter; Kaganskiy, Arsenty; Schall, Johannes; Burger, Sven; Rodt, Sven; Reitzenstein, Stephan
Abstract : Chiral light–matter interaction can lead to directional emission of two‐level quantum emitters in waveguides (WGs). This interesting physics effect has raised considerable attention in recent years especially in terms of on‐chip quantum systems. In this context, this work focuses on tailoring single semiconductor quantum dot–waveguide (QD–WG) systems to emit single photons with high directionality. Low‐temperature in situ electron‐beam lithography enabled by cathodoluminescence mapping is used to select suitable QDs and to integrate them deterministically into linear WG structures at specific chiral points determined by numerical calculations. Excitonic and biexcitonic emission is observed from the fabricated QD–WG structure in a confocal micro‐photoluminescence setup enabling the optical characterization in terms of directional emission of circularly polarized photons emitted by integrated QDs. The results show a high degree of anisotropy on the level of 54% for directional QD emission and antibunching in autocorrelation experiment confirming the fabricated QD–WG system, which is a prerequisite for using this effect in advanced applications in integrated quantum circuits. Abstract : Single‐photon directional emission for on‐chip integrated quantum networks is demonstrated using deterministically integrated quantum dot in a multimode waveguide structure realized in GaAs‐based material system. The directional emission is achieved for exciton and propagating modes due to chiral coupling effect which occurs for highly off‐center circularly polarized quantum emitter.